A investigação da prática de monitores em um observatório astronômico: subsídios para a formação - Barros, Lucas Guimarães; Langhi, Rodolfo; Marandino, Martha (Sociedade Brasileira de Física, 2018)
Abstract The present research is focused in the study about the training of monitors in communication of astronomy, having as main objective to point relevant elements to the training of monitors from an experience in a local astronomical observatory. For this, we used questionnaires, semi-structured interviews and observation of the field activities of the monitors, taking as a reference the data analysis the content analysis. Among the findings, it was noticed the motivating aspect of monitoring found in outreach activities, in addition to the experiences from this rule. Were also mapped some difficulties concerning the monitor interaction with the public and with the staff, the predominance of training focused on interaction between veteran monitor and beginner monitor, in addition to experiences from the practice of monitoring in place, allowing the delimitation of a set of elements that would constitute the monitor profile in these locations.

Resumo A presente pesquisa está centrada no estudo sobre a formação de monitores em espaços de divulgação da Astronomia, tendo como objetivo principal elencar elementos pertinentes à formação de monitores a partir de uma experiência em um observatório astronômico local. Para isso, utilizou-se questionários, entrevistas semiestruturadas e observação das atividades de campo dos monitores, tomando-se como referencial de análise dos dados a Análise de Conteúdo. Dentre os resultados encontrados, percebeu-se o aspecto motivador da monitoria encontrado nas atividades de divulgação, além das experiências oriundas dessa atuação. Foram mapeadas também algumas dificuldades concernentes à interação do monitor com o público e com a equipe, a predominância de uma formação focada na interação entre monitor veterano e monitor novato, além de experiências advindas da prática da monitoria no local, permitindo a delimitação de um conjunto de elementos que viriam a constituir o perfil do monitor nesses locais.
The investigation of the practice of monitors in an astronomical observatory: contributions to the training
Keywords: Training of monitors; Scientific communication; Astronomy Education; Non Formal Education; Science Teaching; Formação de monitores; Divulgação científica; Ensino de Astronomia; Educação Não Formal; Ensino de Ciências